Analysis of Tax Court Decisions Over the Deemed Interest Revenue Dispute From Intragroup Interest-Free Loans - Handayani, Dian Tri; Alfansuri, Lith; Mayangsari, Sekar (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research aims to explore tax disputes related to Deemed Interest Revenue of interest-free intra-group loans; an issue that has persisted over time due to regulatory inconsistencies. In 2023, tax revenue contributed significantly to Indonesia’s state income, with 67% of total revenue sourced from taxes. Despite the positive growth in tax collection, the self-assessment system in Indonesia creates opportunities for non-compliance, leading to tax audits by the Directorate General of Taxes (DJP) to ensure legal adherence. However, tax audits often result in disputes between taxpayers and the DJP, particularly over the interpretation of tax regulations. One recurrent dispute involves the tax treatment of interest-free loans, which lacks clear regulatory guidance. Previous studies show a high rate of DJP losses in court over these cases, raising concerns about the effectiveness of the current legal framework. This research will analyze court rulings, comparing the DJP’s and taxpayers’ perspectives on Deemed Interest Revenue of interest-free loans to identify factors that contribute to DJP’s success or failure in tax disputes. The findings aim to provide recommendations to improve DJP’s strategies in court, reduce the number of disputes, and enhance tax compliance.